GABAA receptor binding molecules from Traditional Chinese Medicine: An in silico approach - Meng Lv; Xue Tao Wang; Kun Li; Yue Lan Wang (Bangladesh Pharmacological Society, 2014)
The advents of how anesthesia works have helped in the discovery of anesthetic target protein. One such target protein named ?-aminobutyric acid (GABAA), which is the chief inhibitory neurotransmitter in the mammalian central nervous system. Asparagine at 289 position of GABAA protein within TM2 is important for its anesthetic function. This study explores Traditional Chinese Medicine (TCM) against ASN 289 of GABAA for novel anesthetic compounds. The in silico approach showed gastrodin out of all compounds to be the best compound to start further analysis. It is a potential anesthetic compound suitable for the development of new drug.